Sosialisasi dan Pendekatan Program Studi Peternakan PSDKU UNPATTI Maluku Barat Daya pada Sekolah SMK.N 7 Maluku Barat Daya - Juwaher Makatita; Heryanus Jesajas; Asmirani Alam; Inggrid Welerubun; Jecklin Lainsamputy; Barnabas Gairtua; Albertus Sairudy; Risart L. Dolewikou; Arnold Ismael Kewilaa (Jurnal Kabar Masyarakat, 2023)
The socialization process is an effort by the livestock study program to introduce and get closer to the community outside. Implementation of community service for the PSDKU UNPATTI Animal Husbandry Study Program, Southwest Maluku Regency was carried out at the SMK. The service approach is carried out by coming directly to the target school and having the theme of the school principal then discussing the purpose of the activities of the PSDKU UNPATTI Animal Husbandry Study Program, Southwest Maluku Regency. Meanwhile, the second stage was implementing community service by presenting socialization material for the PSDKU UNPATTI Animal Husbandry Study Program, Southwest Maluku Regency. This process of community service is specifically for students of SMK.N 7 Southwest Maluku who are in grade 3 so that the aim of introducing the Animal Husbandry Study Program can be clearer and is expected to become a benchmark for them to be able to continue their studies in the PSDKU UNPATTI Animal Husbandry Study Program Southwest Maluku Regency. Results of the implementation of socialization in vocational schools. N 7 Southwest Maluku is running well according to what has been designed together with the livestock study program service team.